수록 한지의 초지방식과 도침이 강도적 성질에 미치는 영향 - 전철; Cheol Jeon (목재공학, 2002)
According to the result of the experiment, except that Oebal Hanji making, which does not consider the fiber orientation, has a smaller difference between its strength of width and length direction than of Ssangbal Hanii making, there is not a significant difference between Oebal Hanji making and Ssangbal Hanji making. In addition, even though Oebal Hanji making produced indigenous technique is generally felt sturdy because its absolute strength is enhanced by applying fine materials and overlaying several sheets of paper, its relative strength, which is expressed in an index, is not far beyond that of Ssangbal Hanji making Study on the effect of Dochim revealed that Dochim improves remarkably folding endurance and enhances breaking length and the burst strength. Especially, Dochim increase tensile strength. It was also revealed that, indigenous Oebal Hanji making, the higher the number of sheets of paper overlaid is, the higher the tear strength is the increase relatively higher than those of other types of strength. Consequently, Dochim treatment greatly reinforces the imperfect strength of indigenous Hanji. We consider that if we apply Dochim treatment to Ssangbal Hanji making it may bring about abnormal imbalance of strength. We can benefit from the characteristic strength of Oebal Hanji making only when performing paper making and Dochim considering fiber orientation. 본 시험은 외발뜨기 한지와 쌍발뜨기 한지의 물리적 특성과 도침이 지질에 어떠한 영향을 미치고 있는지를 구명하고자 검증된 토착한지와 오늘날 전통식으로 제조한 한지, 그리고 개량 한지를 대상으로 했다. 외발뜨기 한지는 치우치지 않는 강도적 특성 때문에 실제 사용할 때, 강하고 질기며 잘 해어지지 않는 종이임을 알 수 있었다. 이처럼 질기다고 느껴지는 것은 좋은 원료와 토착식 제법으로 여러 장 겹쳐서 절대적인 강도를 향상 시켰기 때문이었다. 그러나 상대적 강도인 지수비교에서는 기타 한지와 큰 차이가 없었다. 도침은 내절도를 두드러지게 향상시키며 열단장과 파열지수를 높이는 역할을 했다. 특히 열단장(인장강도)의 향상을 가져왔다. 섬유 배향성을 고려하지 않고 초지한 외발뜨기 한지를 쌍발뜨기 한지와 비교해 보면 가로·세로의 강도 차이가 약간 적다는 것 외에 특별히 뛰어난 점이 없다는 것을 알 수 있었다.